Radiologic guide to orthopedic devices - Hunter, Tim B.; Wild, Jason 1978- (Cambridge medicine, 2017)
Orthopedic devices improve the quality of life of millions of people, and show up on radiographs and cross-sectional imaging studies daily. This text will familiarise radiologists with the indications, applications, potential complications, and radiologic evaluation of many medical devices. The book offers a complete discussion of fracture fixation, joint arthroplasty, and orthopedic apparatus of the neck and spine, including the cervical, thoracic, and lumbar spine. It also provides detailed overviews of devices used for common dental disease, covers the general principles applicable to complications of orthopedic devices, foreign body ingestions, insertions and injuries, and details quality assurance issues concerning the manufacture and distribution of devices. Featuring a large gallery of apparatus for reference, an extensive glossary of terms and a list of manufacturers, Radiologic Guide to Orthopedic Devices is an essential resource for radiologists, orthopedists and emergency medicine physicians. Regular updates to the topics covered will be available on http://www.medapparatus.com